KONSELING GIZI DAN PERUBAHAN PERILAKU PASIEN DISLIPIDEMIA YANG MENDAPAT BOOKLET DAN LEAFLET DI RSI SITI KHADIJAH PALEMBANG - Luthfiyah, Nisrina; Susyani, Susyani; Telisa, Imelda (JURNAL MEDIA KESEHATAN, 2019)
Background: Dyslipidemia is a disorder of lipid metabolism that characterized by the increasing or decreasing lipid fraction plasma. A dyslipidemia may be caused by genetic, age, gender, nutritional intake and smoking habit. Lipid level abnormality is one of the risk factors for cardiovascular and metabolic disease. Management of dyslipidemia includes pharmacological and non-pharmacological therapy that can be supported through nutritional counselling. Objective: The study is to know the effect of nutritional counseling on the behavior of dyslipidemia patients who received booklet and leaflet at Siti Khadijah Islamic Hospital in Palembang. Design: The research design is a quasi-experiment with a pretest and posttest. The research was conducted on January until March 2019. The data analysis uses the Wilcoxon and Mann Whitney tests. Results: Wilcoxon test result shows that nutritional counseling in both groups equally gave effect to knowledge, attitudes and actions. Mann Whitney Test conducted on both groups of knowledge obtained p value of 0.274, the attitude obtained p value of 0.010 and the action obtained p value of 0.065. Conclusion: There was no difference between booklet and leaflet groups, to increase their knowledge and action, however there is a difference between booklet and leaflet groups to attitude improvement of booklet and leaflet groups, where leaflets influence more in increasing a better respondent attitudes to implement dyslipidemia diet.